This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since lo g b a = lo g a b lo g a a = lo g a b 1 (change of base formula), our equation becomes lo g a b + lo g a b 1 = 3 1 0 . Let lo g a b = x . Therefore, x + x 1 = 3 1 0 . Solving for x , we get x = 3 1 or x = 3 . Divide this into two cases:
Case 1 ( x = 3 1 ): Since lo g a b = 3 1 , a 3 1 = b . Therefore, a = b 3 . Since a b = 6 4 , ( b 3 ) b = 6 4 . Solving for b , we get b = 2 .
Case 2 ( x = 3 ): Proceeding in the same manner as we did in Case 1, we eventually get a 3 = b . Therefore, a = 3 b , so 3 b b = 6 4 = 2 6 . Cubing both sides, b b = 2 1 8 , which does not produce any integer solutions.
We can easily see that b = 2 is the only solution for b . From case 1, a = b 3 , so a = 8 . Our final answer is a + b = 8 + 2 = 1 0 . ■